Electronic Module Development Science-Based Learning Flipbook Theory System Breathing in Humans for Student Class VIII SMP/MTs - El Minahussaniyyatul Ula; Paidi Paidi; Jumadi Jumadi (Jurnal Penelitian Pendidikan IPA, 2023)
This research is motivated by the need for teaching materials in the form of science learning modules that utilize information and communication technology. This study aims to develop an electronic module (E-Module) based on flipbook material on the human respiratory system for class VIII SMP/MTs students. The method used in this study uses a 4D development model (Define, Design, Development and Dissemination). In this study was limited only to the stage of small-scale trials. The instruments used are interviews as an initial needs analysis, a validation questionnaire on the feasibility of the E-Module and a student response questionnaire to the E-Modul. The data analysis technique is descriptive qualitative analysis. To find out the results of the product feasibility test, it was assessed by 3 material experts, 3 media experts and 1 science teacher and the responses of seven students of MTs TQ El-MunaQ Pajangan Bantul. The data from the product feasibility analysis were assessed by material experts, media experts and science subject teachers by calculating the percentage of achievement in each component, namely the feasibility of the material obtained by an overall average of 95.34% with the "very feasible" category, media feasibility obtained on average an overall average of 87.27 % with the "very feasible" category, the assessment of science subject teachers obtained an overall average of 73.33% with the "adequate" category. Then the results of student responses by calculating the percentage of achievement in each component obtained an overall average of 91.8%. Based on these data, it can be concluded that the flipbook -based E-Module material on the human respiratory system for class VIII SMP/MTs students is feasible to use and students are interested in using it as a science learning medium to support the teaching and learning process.